Credit risk management policy (CRMP) for musyarakah profit and loss sharing contracts (MPLSc) : a case study of an Islamic bank in Malaysia. - Rosnah Omar (IIUM Institute of Islamic and Finance, International Islamic University Malaysia, 2016)
Historically, the Islamic Banks (IBs) had less emphasis on and involvement in Musharakah Profit and Loss Sharing contracts (MPLSc) as they were more concerned with the associated risk in equity investments. This was partly attributed to inadequate knowledge and experience in managing the equity investment risk. As a recent development by IBs to undertake equity investment, it is pertinent that the procedure to formulate the Credit Risk Management Policy (CRMP) framework was studied in this research. The primary objective of the policy research was to explore and describe on the distinctive Shariah Rule Compliant (SRC) characteristic with the salient features of credit risk assessment (CRA) with the credit risk management (CRM) process on the risk sharing principles (RSP) of MPLSc. Considering the limitation of empirical research reviews and lack of available data to explore on this issue, the case study research methodology with semi-structured interviews was adopted in this research. The research objectives and questions explored on the “risky "perception of MPLSc” as well as the extant related theoretical framework with the description provided by the key representatives of an Islamic Bank in Malaysia (IBM) as interview respondents. The IBM's equity investment in the Musharakah Project Finance (MPF) was evaluated with the project economics and equity investment management. The data analytics on SRC by Shariah Department (SD) in the IBM enhanced the CRMP framework as compared with conventional practice. The comparative review was undertaken with the Conventional Banks (CBs) on credit risk management process which was deemed similar based on regulatory and economic capital management. The semi-structured interviews was to gather the sample data on how the IBM identify, qualify, quantify, manage, monitor and report the RSP for MPLSc with capital management that included the examination of regulatory guidelines and standards in the regulated financial industry. The qualitative data analytics were derived from the identification of the credit risk of the equity investment that was reviewed with the determinant factors that were collated as the research findings. The findings described the ethical behaviour of Shariah compliant adherence by IBM based on the joint-venture contractual obligations. The main contributions were the enhancement from the theoretical framework with the gap analysis in the literature review to redefine the credit risk management process in managing equity investment risk. Finallly with the “CRMP for MPLSc in IB” an incentive was provided in RSP for MPLSc as an alternative financing in equity investment in the IBM.